Tradisi Lisan Ulelean Pare sebagai Penguatan Pendidikan Karakter Berbasis Kearifan Lokal Di Sekolah Dasar - Panggalo, Iindarda Sangkung; Palimbong, Stefani Marina (Publikasi dan UKI Toraja Press Universitas Kristen Indonesia Toraja, 2025)
This study aims to explore the character values found in the oral tradition of Ulelean Pare from Toraja and how to integrate them into character education in elementary schools. Ulelean Pare is a collection of traditional stories passed down through generations, rich in moral messages such as honesty, responsibility, courage, empathy, and cooperation. This research uses a descriptive qualitative approach with in-depth interviews, and literature studies. The results show that Ulelean Pare has strong potential as a culturally relevant and engaging medium for character education among children. Integrating these stories into learning processes provides dual benefits: reinforcing character education and preserving local culture. Therefore, the Ulelean Pare tradition needs to be revitalized as a strategy for culture-based education.